0194 Circulatory system disease mortality among French uranium miners. (23rd June 2014) - Drubay, Damien; Caër-Lorho, Sylvaine; Laroche, Pierre; Acker, Alain; Laurier, Dominique; Rage, Estelle
Abstract : Objectives: There is currently no consensus for an association between risk of Circulatory System Diseases (CSD) and low exposure to ionising radiation. The aim is to study the relationship between CSD mortality and radon exposure in the French cohort of uranium miners considering classical CSD risk factors. Method: The French cohort includes 5086 uranium miners followed from 1946 through 2007. Among the 1935 deaths, 442 were from CSD, including 167 cases of IHD and 105 cases of CVD. Annual radon exposures were assessed individually. A nested case-control study was performed to collect individual information concerning classical CSD risk factors (weight, height, smoking status, blood pressure, blood glucose and cholesterolemia) from medical files for 76 cases of death from CSD (including 26 from IHD and 16 from CVD) and 237 controls, matched for attained age and birth date and counter-matched for cumulative radon exposure. Results: In the whole cohort, a significant association with cumulative radon exposure was observed for CVD mortality, but not for CSD or IHD mortality. In the case-control study, no significant unadjusted Odd-Ratio for cumulative radon exposure was observed for any endpoint. Analyses adjusted on CSD risk factors, for which missing data do not exceed 25%, are ongoing. Conclusions: The issue of CSD associated to ionising radiation is crucial for radiation protection. The present study, allowing to consider individual data on major classical CSD risk factors, will contribute to improve knowledge on the effects of low dose exposure.